(untitled)
The Eurosystem's large-scale asset purchases (quantitative easing, QE) induce a strong and persistent increase in excess reserves in the euro area banking sector. These excess reserves are heterogeneously distributed across euro area countries. This paper develops a two-country New Keynesian model calibrated to represent a high- and a low-liquidity euro area member to analyze the macroeconomic effects of (QE-induced) heterogeneous increases in excess reserves and deposits in a monetary union. QE triggers economic activity and increases the union-wide consumer price level after a negative preference shock. However, its efficacy is dampened by a reverse bank lending channel that weakens the interest rate channel of QE. These dampening effects are higher in the high-liquidity country. We find similar results in response to a monetary policy shock. Furthermore, we show that a shock in the form of a deposit shift between the two countries, interpreted as capital ight, has negative (positive) effects for the economy of the country receiving (losing) the deposits., address = Düsseldorf, author = Maximilian Horst and Ulrike Neyer and Daniel Stempel, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, isbn = 978-3-86304-345-2, keywords = E51; E52; E58; F41; F45; 330; unconventional monetary policy; quantitative easing (QE); monetary policytransmission; excess liquidity; credit lending; heterogeneous monetary union; New Keynesianmodel, language = eng, number = 346, publisher = Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), title = Asymmetric macroeconomic effects of QE-induced increases in excess reserves in a monetary union, type = DICE Discussion Paper, url = https://hdl.handle.net/10419/222346, year = 2020